Millennial Consumer Preferences in Social Commerce Web Design - Anaya-Sánchez, Rafael (2020)
Purpose – Considering the context in which social commerce has changed the way consumers search for information and share experiences, the objective of this study is to understand how three factors of web design (usability, functionality, and sociability) influence consumers’ cognitive and affective assessments and affect their intention to buy.  Design/methodology/approach – Using the PLS technique on a sample of 230 millennials who are regular social commerce users, this study is adapted to the social context of the existing literature on website quality, as well as theories of social learning and consumer intention to buy.  Findings – We used the results to compare the study’s 9 hypotheses, thereby linking variables of web design and socialization in e-commerce environments with components of social learning theory.  Originality/value – This article expands the understanding of the influence of design in social network website environments on consumer assessments and, consequently, their intention to buy, highlighting the importance of design for affective assessments. It also provides relevant information to professionals on how to design their websites to improve consumer purchase attitudes and behaviors, allowing them to focus on how to improve the user experience through web design within the context of continuously changing devices and consumer preferences.